Supervision of Madrasah Principal on the Implementation of English Learning Evaluation - Liza Tazkiah; Suswati Hendriani; M. Yusuf Salam; Asmendri Asmendri; Devi Aisyah (Program Studi Manajemen Pendidikan Islam Institut Pesantren KH Abdul Chalim Mojokerto, 2022)
This article aims to describe the learning evaluation by English teachers and the supervision of madrasah principals using phenomenological research with a qualitative approach. It was conducted at MTsN in Tanah Datar Regency, namely MTsN 1, MTsN 2, and MTsN 3 Tanah Datar. A total of 10 research informants, including the principal of the madrasa and English teachers, were used. The data collection involves in-depth interviews, participatory observation, and documentation studies. Meanwhile, the data technique used was a source and technical triangulation. The results showed that: 1) Evaluation of learning processes and outcomes, in addition to language, was practised by English teachers. The strategies and developments include formative, summative, placement, and diagnostic evaluations. Furthermore, the evaluation of language learning comprises the domain of knowledge, attitudes, and skills. 2) There are several forms of supervision of the madrasah principal on the evaluation of learning, namely supervision of discipline, motivation, training, teacher performance, and work relations.